TEACHER MANAGEMENT IN INCLUSIVE EDUCATION: STRATEGIC HUMAN RESOURCE PRACTICES IN AN ISLAMIC EARLY CHILDHOOD SCHOOL - Murniyanti Ismail (Sasangga: Jurnal Pendidikan dan Pembelajaran, 2026)
Teacher management remains one of the greatest challenges in implementing inclusive early childhood education, particularly in private institutions operating with limited institutional support. This study explores how a pioneering inclusive Raudatul Athfal in South Kalimantan, Indonesia, strategically manages teacher empowerment and professional development to sustain inclusive educational practice. Employing a qualitative single-case study, data were collected through semi-structured interviews with 28 participants, classroom observations, and document analysis. Guided by Strategic Human Resource Management and Professional Capital Theory, the findings reveal a sequential management process comprising values-based recruitment, leadership-driven professional learning, developmental supervision, and knowledge regeneration to sustain professional capacity despite teacher turnover. These strategic practices were subsequently enacted through three forms of professional practice: teachers exercised professional judgment in individualized pedagogy, extended inclusive practice through multidisciplinary collaboration, and transformed parental and community perceptions of disability through sustained engagement. The study extends Strategic Human Resource Management by demonstrating that, in resource-constrained inclusive schools, teacher management functions as a process of creating and sustaining professional capital. The findings provide practical insights for strengthening teacher management policies in inclusive early childhood education, particularly in low-resource educational settings.